2016
DOI: 10.1084/jem.20160447
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen activation of microglia underlies the sexually dimorphic differences in Nf1 optic glioma–induced retinal pathology

Abstract: Toonen et al. show that estrogen increases microglia-mediated retinal damage in neurofibromatosis-1 (Nf1) optic glioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Moreover, several studies have suggested that girls with NF1‐optic gliomas are more likely to experience vision loss and require treatment. Using Nf1 optic glioma mice, this sexually dimorphic effect was shown to be partly due to female gonadal sex hormones acting on microglia to produce inflammatory mediators that damage the optic nerve . In addition to serving as robust platforms for preclinical drug discovery and validation, these GEM strains may be useful for risk assessment strategies aimed at identifying children mostly likely to develop optic gliomas or experience vision loss.…”
Section: The Nf1 Gene and Optic Gliomasmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, several studies have suggested that girls with NF1‐optic gliomas are more likely to experience vision loss and require treatment. Using Nf1 optic glioma mice, this sexually dimorphic effect was shown to be partly due to female gonadal sex hormones acting on microglia to produce inflammatory mediators that damage the optic nerve . In addition to serving as robust platforms for preclinical drug discovery and validation, these GEM strains may be useful for risk assessment strategies aimed at identifying children mostly likely to develop optic gliomas or experience vision loss.…”
Section: The Nf1 Gene and Optic Gliomasmentioning
confidence: 99%
“…Female Nf1–OPG mice that are more prone to visual impairment have threefold more microglia than their male counterparts. This retinal pathology is reversed by pharmacologic inhibition of microglial estrogen receptor‐β (ERβ) function using minocycline in female Nf1–OPG mice . These findings suggest that future endeavors should be aimed at developing treatment strategies promoting RGC survival and moving these exciting preclinical pharmacological interventions into clinics.…”
Section: Future Directions For Nf1‐associated Opg Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Nf1‐ mutant RGCs, by virtue of their impaired neurofibromin function, have baseline reduced levels of intracellular cAMP, which lowers the threshold for RGC death in the setting of neuroinflammatory or neurotoxic stimuli (Brown et al, ) (Figure c). Second, specifically in female mice, gonadal estradiol acts through the estrogen receptor β (ERβ) to stimulate Nf1‐ mutant microglia, thereby causing Nf1 ‐mutant RGC death, thinning of the RNFL (which comprises RGC axons), and decreased visual acuity (Diggs‐Andrews, Brown, Gianino, Rubin, et al, ; Toonen, Solga, Ma, & Gutmann, ). Sexually dimorphic retinal pathology in Nf1 optic glioma mice is independent of tumor size and can be corrected by pharmacologic inhibition of microglial activation, ERβ blockade, or chemical or surgical ovariectomy (Toonen, Solga, et al, ).…”
Section: Insights From Nf1 Gem Modelsmentioning
confidence: 99%
“…In both humans and mice, vision loss from optic gliomas is caused by loss of RGCs. In mice harboring Nf1 optic gliomas, there is a stereotyped pattern of visual system pathology, beginning with RGC axonal damage, followed by increased RGC apoptosis and RNFL thinning, and culminating in decreased visual acuity (Hegedus et al, 2009;Kim, Ju, Hegedus, Gutmann, & Ellisman, 2010;Toonen, Ma, et al, 2017).…”
Section: Nf1 Optic Glioma Vision Loss Is Sexually Dimorphicmentioning
confidence: 99%